Optimalisasi Peran TP-PKK Kecamatan Jambi Timur dan Kecamatan Paal Merah Dalam Rangka Meningkatkan Derajat Kesehatan Masyarakat Berbasis Keluarga - Hubaybah Hubaybah; Herwansyah Herwansyah; Vinna Rahayu Ningsih (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Empowerment and Family Welfare (PKK) is a group whose role is to foster community families both in urban and rural areas that can produce synergies for independent prosperous families by improving mental-spiritual life behavior by living and practicing Pancasila. Some public health issues that can be the top priority of TP-PKK at the sub-district level to be considered, include maternal and child health, smoking behavior, health of pregnant women, vaccinations for toddlers, adolescent and school child health, residential environmental health, nutrition for family members and issues related to social epidemiology (disease incidence based on community characteristics). Some of these issues will be used as material for understanding community service activities in 2 sub-districts in Jambi City - East Jambi District and Paal Merah District. These assistance activities include lectures and questions and answers, simulations in class and simulations in the field (family). This community service activity is carried out in the span of time in July and August 2019, followed by the monitoring and evaluation stages in September and October 2019. The stages of this activity include planning, implementation and accompanied by monitoring and evaluation activities. The results of community service include TP-PKK members at the district level to collect data on healthy families by using healthy family diaries.